Count What All Joy?: The Translation of peirasmós in James 1.2 and 12 - Bowden, Andrew M. (The Bible translator, 2014)
This article argues that it is wrong to translate πειρασμός with two different meanings, first as “trials” in James 1.2 and 12 and then as “temptations” in 1.13. Rather, πειρασμός is best translated as “temptation” in each verse. The author first examines the genre of James, then looks at both the immediate context and the broader context of the epistle. He concludes that, since James focuses on temptation and sin throughout, the best translation for the term in 1.2 and 12 is “temptations.”